2022
DOI: 10.1002/dta.3249
|View full text |Cite
|
Sign up to set email alerts
|

Detection of insulin analogues and large peptides >2 kDa in urine

Abstract: Insulin analogues and large bioactive peptides may be used by athletes to enhance performance and are banned by the World Anti‐Doping Agency (WADA). In addition to insulin analogues, the large peptides include a structurally diverse set of peptides including analogues of growth hormone releasing hormone (GHRH), insulin‐like growth factor‐1 (IGF‐1), and mechano‐growth factor (MGF). Detection of this class of peptides is difficult due to their absorptive losses and presence at very low concentrations in urine. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Along with the development of increasingly powerful mass spectrometers with very high resolution (> 100,000 FWHM), it is now possible to simplify sample preparation to the extent that less pure extracts can be analysed without jeopardizing the required specificity 25 . Samples prepared in this way are generally not suitable for analysis with nano‐LC systems, but modern normal‐flow systems have demonstrated sufficient sensitivity and robustness to achieve the mandatory MRPLs in doping controls 7,8,14,16,19 . The present method is designed as an initial testing procedure, which ideally covers different (if not all) prohibited peptides in one analytical approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the development of increasingly powerful mass spectrometers with very high resolution (> 100,000 FWHM), it is now possible to simplify sample preparation to the extent that less pure extracts can be analysed without jeopardizing the required specificity 25 . Samples prepared in this way are generally not suitable for analysis with nano‐LC systems, but modern normal‐flow systems have demonstrated sufficient sensitivity and robustness to achieve the mandatory MRPLs in doping controls 7,8,14,16,19 . The present method is designed as an initial testing procedure, which ideally covers different (if not all) prohibited peptides in one analytical approach.…”
Section: Discussionmentioning
confidence: 99%
“…These methods are very specific and selective due to the complementary combination of immune extraction, liquid chromatographic separation and detection by (high‐resolution/tandem) MS. But due to the laborious sample preparation steps, recently also more simplified approaches were developed, which also meet the criteria outlined in mandatory WADA documents 16–19 . Most of these assays focus on urine analysis or are limited to one class of peptides (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Performance‐enhancing peptidic drugs and drug candidates, which are prohibited in elite sports, are potentially detectable in blood samples as well as in urine samples. While blood samples own benefits regarding the expected higher concentrations as well as the detection of the non‐metabolised intact drug, urine samples still represent the most frequently collected specimens in doping controls due to good retrospectivity of low molecular doping agents 1–4 . Thus, effective and simplified detection methods for urine are still desirable for most doping control laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Noteworthily, these hybrid methods are very specific by combining the selectivity of antibodies, the separation power of LC and high-resolution/high mass accuracy MS. Additionally, multiplex approaches are realised for several different classes of peptides, which enable already comprehensive initial testing procedures (ITPs). 2,11,12 These methods already reported on the option of replacing the immune extraction protocol by several other processing steps such as ultrafiltration, solid-phase extraction (SPE), etc. Nevertheless, most of these methods are characterised by laborious and costly sample preparation and impede the analysis of high sample numbers with short turnaround times (high throughput).…”
mentioning
confidence: 99%
“…The target analytes including sermorelin, sermorelin metabolite (3-29-NH 2 ), CJC-1295, and tesamorelin were analyzed in PRM mode, and LODs between 5 and 25 pg/ml were reported, presumably facilitated by enhanced recoveries and superior chromatographic as well as ionization conditions, warranting further investigations also concerning additional metabolic products and TCs. Similarly, Cox et al reported on a multi-analyte ITP employing ultrafiltration (3 kDa cutoff)combined with mixed-anion exchange (MAX) SPE and LC-QqQ-MS analysis 70. A volume of 4 ml of urine was centrifuged, ultrafiltrated to a retentate volume of 100-250 μl, and solid-phase extracted using a microelution device, and the diluted eluate was injected onto a C-18 analytical column (2.1 Â 50 mm, 1.7 μm particle size).…”
mentioning
confidence: 99%